Global landscape analysis of reuse and refill solutions - Moss, Ellie; Gerken, Kristina; Youngblood, Kathryn; Jambeck, Jenna R. (Frontiers in Sustainability, 2022)
One important strategy to address plastic pollution is replacing disposable items with reusable ones and creating systems to support the circulation, cleaning and reuse of these items. The Global Landscape of Reusable Solutions was created to understand the evolution, current state, and potential environmental benefits of reuse and refill solutions being provided in nine distinct categories. The Landscape is a consistently updated dataset created through desktop research by researchers in seven geographic regions and engagement with experts around the world. As of June 10, 2022, the Landscape identified 1196 solutions operating in 119 countries. The top three categories were 557 Package-Free Shops, 169 Reuse Advocacy Programs (excluding advocacy efforts by for-profit companies in the space), and 155 Reusable Cup & Container Programs. While 52 of the solutions in the global landscape are established or mature, 77.5% (927) are start-ups or small businesses (e.g., Package Free Shops with only one location). Europe has the largest number of reuse solutions with 441, and North America follows with 317. Barriers to growth for reuse solutions include solving for reusable item material and assortment, expanding and integrating reuse infrastructure, willingness of businesses to adopt reuse solutions amid concerns of impact on transaction speed and operations and acceptance by customers; and, in some locations, policies that restrict reusing and refilling containers. Adoption and scaling of reuse solutions can be supported by behavioral campaigns that normalize and promote reuse, better and more available data, sharing examples of successful systems, and increasing knowledge and understanding of reuse system design.